Variability in the Carbon and Nitrogen Uptake Rates of Phytoplankton Associated With Wind Speed and Direction in the Marian Cove, Antarctica - Kim, Bo Kyung; Jeon, Misa; Park, Sang-Jong; Kim, Hyun-Cheol; Min, Jun-Oh; Park, Jisoo; Ha, Sun-Yong (Frontiers in Marine Science, 2022)
Quantifying temporal variabilities in phytoplankton productivity is essential to improving our understanding of the carbon (C) and nitrogen (N) dynamics and energy flows in natural aquatic ecosystems. At 3-day intervals, samples to determine C and N (NO3- and NH4+) uptake by phytoplankton were collected from fixed stations, and by the effect of NH4+ concentrations on phytoplankton communities in December-January 2018/19 in Marian Cove, Antarctica. Considerable fluctuations in the total C and N productivities were observed, which resulted in dynamic changes in the phytoplankton communities and a stronger coupling between distinct phytoplankton biomasses. The increased rate of NO3- uptake coincided with an enhanced C uptake mainly by microphytoplankton (> 20 µm), followed by an increase in NH4+ uptake, and then an increase in NH4+ concentrations observed at the end of sampling. However, the < 2 µm fraction (picophytoplankton) showed little variation in C and NO3- uptake, and the proportions of assimilated NH4+ contributed to more than half of the total inorganic N assimilated. Clearly, the increased NH4+ did not support increased total phytoplankton biomass and C production. Interestingly, after the first two weeks of the sampling period, the C uptake rate decreased rapidly (< 3 mg C m-3 h-1 on 12 January) after a shift to a predominantly easterly wind (> 6 m s-1), during which time the phytoplankton community was replaced by neritic and ice-related species. These findings suggest that the strong temporal shifts in phytoplankton C assimilation were strongly influenced by external forces (wind stress).